Microbiome-Derived Lipopolysaccharide Enriched in the Perinuclear Region of Alzheimer’s Disease Brain - Zhao, Yuhai; Cong, Lin; Jaber, Vivian; Lukiw, Walter J. (Frontiers in Immunology, 2017)
Abundant clinical, epidemiological, imaging, genetic, molecular and pathophysiological data together indicate that there occur an unusual inflammatory reaction and a disruption of the innate-immune signaling system in Alzheimer’s disease (AD) brain. Despite many years of intense study the origin and molecular mechanics of these AD-relevant pathogenic signals are still not well understood. Here we provide evidence that an intensely pro-inflammatory bacterial lipopolysaccharide (LPS), part of a complex mixture of pro-inflammatory neurotoxins arising from abundant Gram-negative bacilli of the human gastrointestinal (GI) tract, are abundant in AD affected brain neocortex and hippocampus. For the first time we provide evidence that LPS immuno-histochemical signals appear to aggregate in clumps in the parenchyma in control brains, and in AD about 75% of anti-LPS signals were clustered around the periphery of DAPI-stained nuclei. As LPS is an abundant secretory-product of Gram-negative bacilli resident in the human GI-tract, these observations suggest (i) that a major source of pro-inflammatory signals in AD brain may originate from internally-derived noxious exudates of the GI-tract microbiome; (ii) that due to aging, vascular deficits or degenerative disease these neurotoxic molecules may ‘leak’ into the systemic circulation, cerebral vasculature and on into the brain; and (iii) that this internal source of microbiome-derived neurotoxins may play a particularly strong role in shaping the human immune system and contributing to neural degeneration, particularly in the aging CNS. This ‘Perspectives’ paper will further highlight some very recent developments that implicate GI-tract microbiome-derived LPS as an important contributor to inflammatory-neurodegeneration in the AD brain